A Theory of Secondary Teachers' Adaptations When Implementing a Reading Intervention Program. (November 2015) - Leko, Melinda M.; Roberts, Carly A.; Pek, Yvonne
This study examined the causes and consequences of secondary teachers' adaptations when implementing a research-based reading intervention program. Interview, observation, and artifact data were collected on five middle school intervention teachers, leading to a grounded theory composed of the core component, reconciliation through adaptation, and four component concepts: program features, teacher qualities, contextual characteristics, and individual student needs. Findings indicated the most skilled implementers' adaptations capitalized on their professional strengths and the strengths of the intervention to provide students with more engaging and responsive instruction. Implications for future research and practice in the implementation of reading intervention programs for secondary students with disabilities are discussed.